(untitled) (Journal of Energy and Safety Technology (JEST), 2024)
Challenges such as unhealthy lifestyles, work-related stress, and lack of awareness about healthy eating exist in all sectors of employment. Workers often cannot engage in physical activities and lack resources to manage stress and maintain mental well-being. Despite existing efforts to promote workplace health, these issues persist, indicating a lack of current implementation strategies. The purpose of this study is to address these gaps by improving the implementation of Lifestyle Medicine (LM) concepts at work. The improved suggestion on implementation is based on LM and aims to promote healthy lifestyles and create supportive work environments. These efforts include health programs, workplace environment modifications, health education campaigns, and relevant policies. Based on a survey involving 28 organizations, the approach focuses on enhancing stress management, social connection, ergonomic features, and physical activity. Hence, this study enhances LM implementation to address persistent workplace health challenges aiming to foster a workplace culture that enhances employee health, productivity, and satisfaction.